Evaluation of a child with suspected nephrolithiasis. Issue 2 (April 2020) - Reusz, George S.; Hosszu, Adam; Kis, Eva
Abstract : Purpose of review: As the incidence of nephrolithiasis in children doubles every 10 years it is becoming a common disease associated with significant morbidity along with considerable economic burden worldwide. The aim of this review is to summarize current data on the epidemiology and causes of renal stones in children and to provide a frame for the first clinical evaluation of a child with suspected nephrolithiasis. Recent findings: Dietary and environmental factors are the driving force of changing epidemiology. Diagnosis should be based on medical history, presenting signs, examination, first laboratory and radiological workup. Ultrasound should be the initial diagnostic imaging performed in pediatric patients while low-dose computed tomography is rarely necessary for management. Metabolic factors including hypercalciuria, hypocitraturia, low fluid intake as well as specific genetic diseases should be explored after the resolution of initial signs and symptoms. Summary: Appropriate initial evaluation, imaging technique, identification of risk factors and other abnormalities are essential for early diagnosis and prevention of stone-related morbidity in children with suspected nephrolithiasis.